Pendidikan Dalam Perspektif I’rab - Hamdy M Zen; Mawardi Djamaluddin (IAIN Ternate, 2022)
This study set out from the author’s considerations which tried to make sense of the meaning of ʾIʿrāb into the essence of education. The purpose of this study is to find out and give understanding about how to realize the value of education as contain in ʾIʿrāb. This study is a qualitative method by employing library research with descriptive analysis approach. The results showed that the contextual values in ʾIʿrāb such as Rafa’, Nashab, Jar, Jazm have the same meaning as education in which they can help us eager to implement educational values to daily life.